2018
DOI: 10.1093/ehjqcco/qcy040
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rivaroxaban vs. warfarin in patients with non-valvular atrial fibrillation and a history of cancer: observations from ROCKET AF

Abstract: In ROCKET AF, a history of cancer was associated with a higher risk of bleeding and non-cardiovascular death, but not ischemic events. The relative efficacy and safety of rivaroxaban compared with warfarin were not significantly different in patients with and without a history of cancer. The results of this study are exploratory and should be taken in context of the study population, which may not be generalizable to those with advanced malignancy. Further investigation is needed to understand optimal anticoag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 23 publications
1
100
0
2
Order By: Relevance
“…However, secondary analyses of these studies in patients with or without a history of cancer or in patients who developed cancer after enrollment have shed some light on DOAC use in the cancer population. In the ROCKET AF study, the efficacy and safety of rivaroxaban and warfarin in 460 patients with history of cancer were similar to those in patients without cancer . In the ATRISTOLE study, the safety and efficacy advantages of apixaban over warfarin in patients without a history of cancer were preserved in those with a cancer history .…”
Section: Introductionmentioning
confidence: 94%
“…However, secondary analyses of these studies in patients with or without a history of cancer or in patients who developed cancer after enrollment have shed some light on DOAC use in the cancer population. In the ROCKET AF study, the efficacy and safety of rivaroxaban and warfarin in 460 patients with history of cancer were similar to those in patients without cancer . In the ATRISTOLE study, the safety and efficacy advantages of apixaban over warfarin in patients without a history of cancer were preserved in those with a cancer history .…”
Section: Introductionmentioning
confidence: 94%
“…However, these recommendations cannot be extended to AF patients with malignances because in randomized clinical trials (RCTs) of DOACs for stroke and systemic embolism prevention in AF, cancer patients were underrepresented. Nevertheless, posthoc analyses of RCTs of DOACs [14][15][16][17] and retrospective population or cohort studies [18][19][20][21][22][23] have shown promising results of DOACs compared to VKAs in non-valvular AF patients with cancer. Therefore, we aimed to systematically assess the available evidences in the literature regarding the safety and efficacy of DOACs in comparison to VKAs in patients affected by non-valvular AF and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of genitourinary varied from 27.14% of the ENGAGE-AF 17 to 40.8% in the ROCKET-AF. 15 GI tract cancer ranged from 16.18% in the ARIS-TOTLE 16 to 33.21% of the ENGAGE-AF population. 17 In the Mar-ketScan analysis, 18 lung cancer was present in 13.1%, GI in 13.9% and genitourinary in 28.7%, this latter proportion being similar to the present study.…”
Section: Discussionmentioning
confidence: 99%